In-situ synthesis and enhanced upconversion luminescence of Y2O3/Y2O2S:Yb3+, Er3+/Tm3+ nanocomposites by reduction of Y2O3:Yb3+, Er3+/Tm3+. (March 2019) - Xu, Linna; Liu, Lijuan; Pan, Kai; Fan, Naiying; Wang, Guofeng; Qin, Weiping
Graphical abstract: Highlights: Y2 O3 /Y2 O2 S:Ln 3+ nanocomposites with enhanced upconversion luminescence were successfully prepared by combining hydrothermal with in-situ synthesis method. The UC luminescence intensity of Y2 O3 /Y2 O2 S:Ln 3+ was much stronger than those of Y2 O3 :Ln 3+ and Y2 O2 S:Ln 3+ . The limit of detetion of glucose level which based on Y2 O3 /Y2 O2 S:Yb 3+, Er 3+ @Au was only 0.066 μmol/L. Abstract: Y2 O3 /Y2 O2 S:Ln 3+ (Ln = Yb, Er and Yb, Tm) nanocomposites with enhanced upconversion luminescence were successfully prepared by combining hydrothermal with in-situ synthesis method. Under 980 nm excitation, the upconversion luminescence intensity of Y2 O3 /Y2 O2 S:Ln 3+ increased, and then declined with the rising amount of sulfur powder. Especially, the Y2 O3 /Y2 O2 S:Ln 3+ nanocomposites can emit brighter upconversion luminescence than those of Y2 O3 :Ln 3+ and Y2 O2 S:Ln 3+ . In terms of Y2 O3 /Y2 O2 S:Yb 3+, Er 3+ nanocomposites which were prepared with 0.025g sulfur powder, an unusual 4 G11/2 → 4 I15/2 and 4 F9/2 → 4 I15/2 transitions of Er 3+ could be observed. Besides, we have constructed a simple upconversion Y2 O3 /Y2 O2 S:Yb 3+, Er 3+ @Au nanocomposite, which can be used for rapid sensing of glucose. The limit of detection of glucose level which based on Y2 O3 /Y2 O2 S:Yb 3+, Er 3+ @Au was only 0.066 μmol/L. The proposed approach, which we have mentioned above, holds a great practical value for diabetes mellitus detection and clinical diagnosis.